2020
DOI: 10.1088/2053-1591/ab7d57
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfur on corrosion behavior of Q235 and 16Mn steel in sodium aluminate solutions

Abstract: This study investigates the effect of sulfur on Q235 steel and 16Mn steel corrosion in sodium aluminate solution. The corrosion rate of Q235 steel and 16Mn steel reaches the maximum respectively when S 2− and S 2 O 3 2− form synergistic corrosion and S 2− is contained alone. But, the size of corroded particles is smaller in the solution containing only S 2 O 3 2− for two kinds of steel. The corrosion rate of 16Mn steel is greater than Q235 steel. Surface corrosion of two kinds of steel is both composed of sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(25 reference statements)
3
7
1
Order By: Relevance
“…While R f decreases with the corrosion time, indicating that the charge transfer is the main control step of corrosion and R f is small due to surface cracking at 4-5 d. At the same time, it found that when corroded for 3 d, the diffusion resistance (W R ) and diffusion exponent (W p ) of the Warburg component (at LF) is 428.5 Ω•cm −2 and 0.39, respectively. These results indicate that the corrosion products are dense and have a great influence on the ions diffusion, and the surface of the electrode has a certain degree of roughness and there is an ion dispersion effect [24,42], which is consistent with the results of SEM and AFM. In fact, faster scale nucleation leads to the appearance of smaller crystals that produce a compact layer.…”
Section: Electrochemical Impedance Spectrumsupporting
confidence: 87%
See 4 more Smart Citations
“…While R f decreases with the corrosion time, indicating that the charge transfer is the main control step of corrosion and R f is small due to surface cracking at 4-5 d. At the same time, it found that when corroded for 3 d, the diffusion resistance (W R ) and diffusion exponent (W p ) of the Warburg component (at LF) is 428.5 Ω•cm −2 and 0.39, respectively. These results indicate that the corrosion products are dense and have a great influence on the ions diffusion, and the surface of the electrode has a certain degree of roughness and there is an ion dispersion effect [24,42], which is consistent with the results of SEM and AFM. In fact, faster scale nucleation leads to the appearance of smaller crystals that produce a compact layer.…”
Section: Electrochemical Impedance Spectrumsupporting
confidence: 87%
“…The X'pert HighScore software was used to analyze the phase composition of the corrosion products, which may be composed of FeS, FeS2, Fe2O3, Fe3O4, Al2O3, MnS2 and NaFeO2 combined with thermodynamic analysis, which is suggested from the previous research [14,24,25] and is basically consistent with the EDS analysis in Figure 3. Although the phase composition of the corrosion products is the same, the peak intensity is different, which indicates that the crystallinity is different.…”
Section: Xrd Analysissupporting
confidence: 70%
See 3 more Smart Citations